Analysis of Phonological Errors in Reading Skills Arabic Text at School - Bayu Wahyu Maulana; M. Rizqi Zainal Islam; Hamza Shoubaki; Tahir Tahir (Journal of Arabic Language Teaching, 2025)
This research is based on the existence of problems related to the low ability of students to recite letters, words, or sentences in Arabic. This study attempts to analyze students' mistakes in reading skills in Arabic texts viewed in terms of phonology. This research is a type of qualitative research with a descriptive research design. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research subjects were Arabic teachers and students of class XI Senior High School 2 Jember. The results of this study are as follows. First, phonological errors in Arabic text reading skills of class XI students in the Senior High School 2 Jember. such as consonant errors in throat groups and tongue groups; vocal errors such as vocal omission errors, vocal change errors, and short long vocal errors; diphthong error; double consonant error, and the fifth is the clothing assimilation error (ال) . Second, the factors that cause language errors in reading skills include linguistic factors and non linguistic factors. Non linguistic factors such as low interest and motivation in language, and lack of application of Arabic.